Avaliação da qualidade de vida visual e da sintomatologia depressiva associada à visão funcional em indivíduos com Doença de Stargardt - Mirela Luna Santana (2018)
INTRODUCTION: Stargardt's Disease (DSTG) is a macular dystrophy usually begins in the first decades of life and progresses to a loss of central vision function. Presumably such symptoms may compromise the performance of daily activities, with repercussions on visual quality of life, depressive state and functional vision. OBJECTIVE: To analyze visual quality of life in individuals with DSGDT, as well as correlate it to the depressive state and the functional vision. PARTICIPANTS AND METHODS: This is a cross-sectional study, conducted in a sample of 41 participants with DSTG and 46 healthy controls, from Hospital São Geraldo, Hospital das Clínicas, Federal University of Minas Gerais (HC-UFMG). The 25-question visual function questionnaire from the National Eye Institute (NEI VFQ-25), Mini International Neuropsychiatric Interview (MINI Plus 5.0), the depressive symptom questionnaires: Beck Depression Inventory (BDI) and the Hamilton Depression Rating Scale (HAM-D), as well as the visual function: visual acuity and manual visual field tests, both of which were measured to calculate functional vision. Comparison of socio-demographic variables, visual quality of life, depression and functional vision were performed using Fisher's exact test with the mid-p method and the MannWhitney-Wilcoxon test. The results of NEI VFQ-25, MINI Plus, BDI and HAM-D were correlated by the Spearman coefficient. The multivariate analysis was performed using the regression tree technique with ANOVA method. RESULTS: A significant difference was observed in all ten subscales and in the final compound (p <0.001), except for the subscale "general health", in the comparison of the means of the NEI VFQ-25 questionnaire between the controls and the DSTG group. There was no significant difference between the two groups regarding the socio-demographic variables. There was also no statistically significant difference in the number of participants with past or present depressive episode evaluated by the MINI Plus 5.0 or the mean scores on the BDI and HAM-D scales between the patients and the controls. However, a correlation analysis showed that the variable that presented the highest correlation with the final score of the NEI VFQ-25 was the depressive symptomatology evaluated by the BDI (rho = -0.49). Others were the family income (rho = 0.37) and functional vision (rho = 0.41). CONCLUSION: DSTG participants presented worse results in functional vision tests and visual quality of life evaluation in relation to controls. Although these patients did not have a higher frequency of depressive episodes when compared to the controls, the depressive symptomatology was highly correlated with loss of quality of life in the patients.